PERAN FATWA DALAM REGULASI DAN TATA KELOLA PRODUK HALAL DI INDONESIA - Muhammad Fiqih Akbar; Ani Faujiah (STAI AN-NAJAH INDONESIA MANDIRI, 2023)
This article discusses the role of fatwas in the regulation and governance of halal products in Indonesia. Fatwas, which are Islamic legal guidelines, have an important role in setting standards and procedures to ensure the halalness of a product. In Indonesia, fatwas are used as a reference in the regulation and assessment of halal products by institutions responsible for halal product governance such as the Indonesian Ulema Council (MUI) and the Halal Product Guarantee Administering Agency (BPJPH).This article will discuss how fatwas are used in the regulation and governance process of halal products in Indonesia. First, the role of the MUI as an institution that issues fatwas regarding halal products will be explained. Then, we will discuss the process of determining a fatwa by the MUI and how the fatwa becomes a reference in assessing halal products by BPJPH. Next, this article will discuss how fatwas play a role as a regulatory instrument in ensuring product halal. Fatwa is a reference in the certification and inspection process for halal products by BPJPH. Apart from that, this article will discuss the role of fatwas in monitoring and enforcing laws against violations related to halal products in Indonesia. Finally, this article will cover the challenges and debates surrounding the role of fatwas in the regulation and governance of halal products in Indonesia. Several controversies have arisen regarding the validity of fatwas and the diversity of interpretations of Islamic law in Indonesia. This article will also present several solutions that can strengthen the role of fatwas in the regulation and governance of halal products Keyword: Fatwa, Regulation, Governance, Halal Products, MUI, BPJPH, Halal, Islamic Law, Indonesia Abstrak: Artikel ini membahas peran fatwa dalam regulasi dan tata kelola produk halal di Indonesia. Fatwa, yang merupakan panduan hukum Islam, memiliki peran penting dalam penetapan standar dan prosedur untuk memastikan kehalalan suatu produk. Di Indonesia, fatwa digunakan sebagai acuan dalam pengaturan dan penilaian terhadap produk halal oleh lembaga-lembaga yang bertanggung jawab dalam tata kelola produk halal seperti Majelis Ulama Indonesia (MUI) dan Badan Penyelenggara Jaminan Produk Halal (BPJPH). Artikel ini akan membahas bagaimana fatwa digunakan dalam proses regulasi dan tata kelola produk halal di Indonesia. Pertama, akan dipaparkan peran MUI sebagai lembaga yang mengeluarkan fatwa mengenai kehalalan produk. Kemudian, akan dibahas proses penetapan fatwa oleh MUI dan bagaimana fatwa tersebut menjadi acuan dalam penilaian produk halal oleh BPJPH. Selanjutnya, artikel ini akan membahas bagaimana fatwa berperan sebagai instrumen regulasi dalam memastikan kehalalan produk. Fatwa menjadi acuan dalam proses sertifikasi dan pemeriksaan produk halal oleh BPJPH. Selain itu, artikel ini akan membahas peran fatwa dalam pengawasan dan penegakan hukum terhadap pelanggaran terkait produk halal di Indonesia. Terakhir, artikel ini akan mencakup tantangan dan perdebatan seputar peran fatwa dalam regulasi dan tata kelola produk halal di Indonesia. Beberapa kontroversi muncul terkait keabsahan fatwa dan keberagaman tafsir hukum Islam di Indonesia. Artikel ini juga akan menyajikan beberapa solusi yang dapat memperkuat peran fatwa dalam regulasi dan tata kelola produk halal. Kata Kunci: Fatwa, Regulasi, Tata Kelola, Produk Halal, MUI, BPJPH, Kehalalan, Hukum Islam, Indonesia